Gut microbiome and circulating bacterial DNA ("blood microbiome") in a mouse model of total parenteral nutrition: Evidence of two distinct separate microbiotic compartments. (June 2022) - Lucchinetti, Eliana; Lou, Phing-How; Lemal, Philipp; Bestmann, Lukas; Hersberger, Martin; Rogler, Gerhard; Krämer, Stefanie D.; Zaugg, Michael
Summary: Background & aims: Total parenteral nutrition (TPN) causes gut atrophy, dysbiosis and leakage of the gut barrier. This study aimed to characterize the gut microbiome in response to different TPNs and tested the hypothesis whether increased gut permeability in TPN would lead to changes in the circulating bacterial DNA ("blood microbiome"). Methods: Male C57BL/6J mice were randomly allocated to the following groups for seven days (1) chow-fed control (C) without jugular vein catheter (JVC, n=6) (2) chow-fed with JVC and infusion of saline (S) (n = 6) (3) Intralipid-based TPN (n-6:n-3 ratio 7:1) (IL, n = 6) (4) Omegaven-based TPN (n-6:n-3 ratio 1:8) (OV, n = 6). Blood was collected by cardiac puncture and feces (stool pellet) were collected from the colon. Blood and stool samples were analyzed by 16S rRNA gene sequencing. Results: TPN administration was associated with a compositional shift in the gut microbial community that involved the expansion of Bacteroidota along with a decrease in gut bacteria belonging to the Firmicutes phylum as compared to chow-fed mice. Gram-negative Verrucomicrobiota and Proteobacteria were also increased in the gut microbiome of mice receiving TPN. Gammaproteobacteria, namely Burkholderiales, were specifically increased in Intralipid-based TPN. On the other hand, Proteobacteria and Actinobacteriota were the dominant taxa in blood samples. The families Comamonadaceae and Burkholderiaceae (both from Burkholderiales order) were increased in the "blood microbiome" of mice with indwelling JVC when compared with chow-fed mice without JVC. The increase in Burkholderiaceae was more pronounced in Intralipid-based TPN. Conclusions: Profound changes in the gut microbiome of mice subjected to TPN occurred, which were not reflected in the "blood microbiome" suggesting that the gut and "blood microbiome" represent two rather distinct separate microbiotic compartments. The parenteral provision of n-3 fatty acids appears to protect against proinflammatory bacteria in the gut and against the increased presence of JVC-associated bacteria as measured by circulating bacterial DNA.